Plasmonic Enhancement of Gold Nanoparticles in Poly(3-hexylthiophene) Organic Phototransistor - Zakaria, R.; Woon, K.L.; Chua, C.L. (IOP Publishing, 2012)
We report an alternative approach to enhance the photoresponsivity of an organic phototransistor by intergrating plasmonic active spherical gold nanoparticles into regio-regular poly(3-hexylthiophene) (P3HT). The photoresponsivity increases from 9 to 21 A/W at a gate voltage of +10 V under illumination of a solar simulator. It is attributed to the enhanced near-field absorption and exciton dissociation near the plasmonic active gold nanoparticles.